From the Bottom Up: Exploring the Rights and Agency of Central Asian Displaced Persons in the World War II Aftermath - Shaakerimova, Malika (Culture and History: Student Research Papers, 2023)
In this article special focus is given to the casefiles of Soviet Central Asian nationals as they relate to the Care and Maintenance program under the International Refugee Organization (IRO). While refugees are often portrayed as void of agency or remain invisible, incidentally, these minorities’ voices and narratives are underrepresented in history of displacement and refugeedom too. The available records of this small group of refugees or displaced persons (DPs) are helpful in capturing their agency through exploring the ways they were navigating through the process of claiming assistance and protection in their particular circumstances.